Water quality monitoring at kuantan river - Norhidayah , Ahmad (2012)
Kuantan River is one of the important rivers in Pahang state which contributes many resources to the community. A study of the Kuantan River water quality was conducted during a period from September 2011 to November 2011. Three sampling stations were selected based on the topography characteristics of the river. A total of nine chemical water quality parameters and three physical parameters were measured. Three physical parameters measured were temperature, conductivity and suspended solid (SS). The nine chemical parameters were pH, dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), chloride, nitrates, phosphate, and heavy metals, i.e. cadmium (Cd), copper (Cu), and lead (Pb). Parameters such as conductivity, dissolved oxygen, temperature and pH were analyzed in-situ measurement while the rest of the parameters analysis conducted in laboratory. The result obtained was compared to the National Water Quality Classes by DOE. In Conclusion, Kuantan River was classified as DOE NWQS Class II water body.